Opioid Utilization and Perception of Pain Control in Hospitalized Patients: A Cross‐Sectional Study of 11 Sites in 8 Countries. Issue 12 (24th July 2019) - Burden, Marisha; Keniston, Angela; Wallace, Mary Anderson; Busse, Jason W; Casademont, Jordi; Chadaga, Smitha R; Chandrasekaran, Sumitra; Cicardi, Marco; Cunningham, John M; Filella, David; Hoody, Daniel; Hilden, David; et al.
Abstract : BACKGROUND: Hospitalized patients are frequently treated with opioids for pain control, and receipt of opioids at hospital discharge may increase the risk of future chronic opioid use. OBJECTIVE: To compare inpatient analgesic prescribing patterns and patients' perception of pain control in the United States and non‐US hospitals. DESIGN: Cross‐sectional observational study. SETTING: Four hospitals in the US and seven in seven other countries. PARTICIPANTS: Medical inpatients reporting pain. MEASUREMENTS: Opioid analgesics dispensed during the first 24‐36 hours of hospitalization and at discharge; assessments and beliefs about pain. RESULTS: We acquired completed surveys for 981 patients, 503 of 719 patients in the US and 478 of 590 patients in other countries. After adjusting for confounding factors, we found that more US patients were given opioids during their hospitalization compared with patients in other countries, regardless of whether they did or did not report taking opioids prior to admission (92% vs 70% and 71% vs 41%, respectively; P < .05), and similar trends were seen for opioids prescribed at discharge. Patient satisfaction, beliefs, and expectations about pain control differed between patients in the US and other sites. LIMITATIONS: Limited number of sites and patients/country. CONCLUSIONS: In the hospitals we sampled, our data suggest that physicians in the US may prescribe opioids more frequently during patients' hospitalizations and at discharge than their colleagues in other countries, and patients have different beliefs and expectations about pain control. Efforts to curb the opioid epidemic likely need to include addressing inpatient analgesic prescribing practices and patients' expectations regarding pain control. Abstract :